2010
DOI: 10.1242/dev.046045
|View full text |Cite
|
Sign up to set email alerts
|

The RNA-binding protein bicaudal C regulates polycystin 2 in the kidney by antagonizing miR-17 activity

Abstract: SUMMARYThe RNA-binding protein Bicaudal C is an important regulator of embryonic development in C. elegans, Drosophila and Xenopus. In mouse, bicaudal C (Bicc1) mutants are characterized by the formation of fluid-filled cysts in the kidney and by expansion of epithelial ducts in liver and pancreas. This phenotype is reminiscent of human forms of polycystic kidney disease (PKD). Here, we now provide data that Bicc1 functions by modulating the expression of polycystin 2 (Pkd2), a member of the transient receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
107
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(117 citation statements)
references
References 59 publications
(85 reference statements)
8
107
1
1
Order By: Relevance
“…Proximal tubules express BICC1 35 and never develop cysts in ANKS6 I747N kidneys, further suggesting that ANKS6 and BICC1 are linked by an unidentified protein complex 15 also involved in cystogenesis. Of note, BICC1 and ANKS6 colocalized in the glomerulus, and there are glomerular cysts in Bicc1 mutant mice, 14,29 as well as in our ANKS6 I747N model of PKD. Alternatively, altered ANKS6-BICC1 interaction through the ANKS6 SAM domain might fail to appropriately recruit other proteins or perturb the formation of complex between ANKS3, ANKS6, and BICC1.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Proximal tubules express BICC1 35 and never develop cysts in ANKS6 I747N kidneys, further suggesting that ANKS6 and BICC1 are linked by an unidentified protein complex 15 also involved in cystogenesis. Of note, BICC1 and ANKS6 colocalized in the glomerulus, and there are glomerular cysts in Bicc1 mutant mice, 14,29 as well as in our ANKS6 I747N model of PKD. Alternatively, altered ANKS6-BICC1 interaction through the ANKS6 SAM domain might fail to appropriately recruit other proteins or perturb the formation of complex between ANKS3, ANKS6, and BICC1.…”
Section: Discussionsupporting
confidence: 51%
“…Results from western blot analysis showed that the global expression of BICC1 was not significantly increased in ANKS6 I747N compared with normal kidneys (Figure 8b). Because BICC1 downregulates the canonical Wnt/β-catenin pathway at the level of dishevelled 2 (DVL2) 13 and stimulates PC2 expression, 14 we compared the expression of these proteins by western blot analysis of kidney protein lysates of ANKS6 I747N (n = 6) and control (n = 6) mice, using GAPDH as an internal control. Results showed significantly increased expression of both DVL2 (Figure 8c) and active β-catenin ( Figure 8d) in ANKS6 I747N kidneys, whereas expression of PC2 was significantly decreased (Figure 8e).…”
Section: Resultsmentioning
confidence: 99%
“…Erst kürzlich konnte eine posttranskriptionale Regulation von Polycystin-2 durch Bicc1 gezeigt werden. Bicc1 reguliert hierbei die Stabilität der Pkd2-mRNA und deren Translationseffizienz durch das Antagonisieren der repressiven Aktivität der miR-17-microRNA-Familie in der 3'-UTR der Pkd2-mRNA [53]. In Embryonen eines Bicc1-Knock-outs (Bicc -/-) wurde eine gestörte Zilienausrichtung beobachtet.…”
Section: Spontanmutationen In Genen Ohne Orthologie Zu Humanen Pkd-genenunclassified
“…First, inhibition of miRNA biogenesis in maturing renal tubules produces numerous tubular and glomerular cysts [2]. Second, aberrant miRNA expression directly contributes to cyst growth in mouse models of PKD [3], and finally, miRNAs regulate the expression of many cystic kidney disease genes [2-4]. …”
Section: Introductionmentioning
confidence: 99%
“…Two groups of miRNAs - the miR-17 and related miRNAs, and the miR-200 miRNA family – have been shown to function as novel regulators of PKD gene dosage [2,4]. These observations raise an intriguing possibility that miRNAs not only regulate renal tubule development but also contribute to cyst pathogenesis through regulation of PKD genes.…”
Section: Introductionmentioning
confidence: 99%